Feasibility and performance of ground source heat pump systems for commercial applications in tropical and subtropical climates. (June 2020) - Roy, Debasree; Chakraborty, Tanusree; Basu, Dipanjan; Bhattacharjee, Bishwajit
Abstract: The feasibility of installation and performance of vertical ground source heat pump (GSHP) systems for heating and cooling of a typical 9000 m 2 office building located in ten metropolitan cities with tropical and subtropical climates are investigated. The heating and cooling loads of the identical building in the ten cities are simulated using the EnergyPlus software. For each location, the design of the GSHP system is performed using the ground loop design (GLD) software, and the performance of the GSHP system is assessed. A multi-year cost analysis is also carried out to assess the feasibility of installation of GSHP systems from an economic point of view. It is found that GSHP systems may not be economically viable for the cities in tropical climates, particularly those near the equator, because of inefficient performance and high cooling demand. Thermal imbalance in soil caused by significantly greater cooling demand than heating demand may further exacerbate the system in tropical cities. However, the implementation of GSHP may turn into a feasible option for some of the tropical cities located near the Tropic of Cancer by adopting special design techniques or including additional hybrid energy sources. GSHP systems seem to be economically feasible and operationally efficient in the cities with subtropical climates where more balance between heating and cooling loads exist. Highlights: GSHP system considered one of the most popular geothermal system for space heating-cooling. GSHP with special design or energy sources a good option near Tropic of Cancer. GSHP system may not be the best option in few cities near equator. GSHP system mostly economical in subtropical cities.